Britain, Germany and the road to the Holocaust : British attitudes towards Nazi atrocities - Wallis, Russell (International library of twentieth century history, 2014)
In the 1930s, the British public's emotional response to the atrocities of the Spanish Civil War, including the bombing of Guernica, shaped the mass-politics of the age. Similarly, alleged German atrocities in World War I against the Belgians and the French had led to campaigns in Britain for donations to support the victims. Why then, was the British public seemingly less concerned with the treatment of Jews in Hitler's Germany? Outlining a 'hierarchy of compassion', Russell Wallis seeks to show how and why the Holocaust met initially with such a muted response in Britain. Drawing on primary source material, Wallis shows why the Nuremberg laws were reported without great protest, along with Kristallnacht and the creation of the Prague Ghetto. Even after the reality of the 'Final Solution' was announced by Anthony Eden to the British Parliament in 1942, the Holocaust remained a footnote to the war effort. Britain, Germany and the Road to the Holocaust is a study of the British relationship with Germany in the period, and a dissection of British attitudes towards the genocide in Europe. -- Provided by publisher.